Relatório do estágio curricular supervisionado em medicina veterinária área de concentração: clínica e cirurgia de equinos - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This report aims to describe the location and activities carried out and monitored during the Supervised Curricular Internship in Veterinary Medicine (ECSMV). In addition to bringing routine activities, it will emphasize cases of acute abdomen caused by a perforating metallic foreign body in the small intestine of a horse and incisional hernia in a horse. The chosen location was Comfort Equi Equine Medical Clinic, located in the municipality of Cruz Alta – RS. The ECSMV was carried out under the supervision of a Veterinary Doctor specializing in Equine Clinic and Surgery Éder Lúcio Bernardi and guidance from Professor Dr. Claudia Acosta Duarte. The period for carrying out the curricular internship was 12 September to December 2, 2022, totaling 450 hours in the field internship, focusing on the Equine Medical and Surgical Clinic. The activities monitored included emergency care, external care, support for hospitalized animals and surgical procedures. They were 56 cases were monitored during the ECSMV period, the most common conditions of digestive, integumentary and locomotor origin. The internship period it was aggregating and useful, combining theory with the practice of clinical and surgical routine equine experience with learning in the classroom, understanding the role of the doctor veterinarian in the clinical area and decision making, based on knowledge theoretical-practical. Throughout the internship period, there was also the opportunity to develop a critical and human sense about the profession, thus adding knowledge of interpersonal relationships, humanity, ethics and honesty during the exercise of the profession of veterinarian.
Curricular internship report supervised in veterinary medicine area of concentration: equine clinic and surgery
Keywords: Horse; Clinic; Cólica; Herniorrafia; Clínica; Cirurgia; Herniorrhaphy; Cavalo; Surgery; Colic; CNPQ::CIENCIAS AGRARIAS